Masculinity and Lying - Vorsatz, Marc; Sanchez-Pages, Santiago; Turiegano, Enrique (Frontiers in Psychology, 2021)
Dishonesty in communication has important economic implications. The standing literature have shown that lying is less pervasive than predicted by standard economic theory. We explore whether biology can help to explain this behavior. In particular, we study whether masculine traits are related to lying and deception in a sender-receiver game. The three masculine traits we study (the second-to-fourth digit ratio, facial morphometric masculinity and the facial width-to-height ratio) have a significant and nuanced association with honesty in strategic communication. These effects operate mostly through social preferences rather than through beliefs about the behavior of receivers.